Flow-field mitigation of membrane fouling (FMMF) via manipulation of the convective flow in cross-flow membrane applications - Zamani, Farhad (2017)
Membrane fouling by particulates is largely driven by permeate drag that causes the foulants to move towards the membrane. Cross-flow is used to induce shear at the membrane surface to mitigate the fouling. This study describes the flow-field mitigation of membrane fouling (FMMF) technique that reduces the fouling based on a judicious manipulation of the flow-field by inclining the channel walls to counter the permeate drag experienced by the foulants. The key mechanism is the additional transverse (i.e., orthogonal to the fluid flow direction) fluid vector caused by a small inclination of the channel walls (on the order of one to a few degrees). Both simulation and experiments confirm the efficacy of FMMF in mitigating fouling at a reduced energy requirement compared with the conventional channels with parallel walls. Simulations over a range of permeate fluxes indicated that a slight inclination angle of 1.15° can give a deposition factor less than that in the conventional channel with parallel walls even at twice the permeate flux. Direct observation through the membrane (DOTM) experiments for fouling using two particle diameters over a range of power inputs showed that the critical fluxes were significantly increased in the FMMF module compared with the conventional module. This study provides a proof-of-concept of the principle underlying FMMF and underscores the potential benefits. The direction for further development and scale-up is suggested.